Oxidation Mechanisms of Electrolyte and Fire Gas Generation Laws During a Lithium-Ion Battery Thermal Runaway - Yao Tian; Xia Zhang; Qing Xia; Zhaoyang Chen (Fire)
Lithium-ion batteries (LIBs) have come to hold ever greater significance across diverse fields. However, thermal runaway and associated fire incidents have undeniably constrained the application and development of LIBs. Consequently, gaining a profound understanding of the reaction mechanisms of LIB electrolytes during thermal runaway is of critical importance for ensuring the fire protection of LIBs. In this study, quantum chemical calculations were employed to construct oxidation reaction models of electrolytes, and a comprehensive summary of the sources of fire gas generation during the thermal runaway of LIBs is presented. During the sequence of oxidation reactions, the -COH functional group emerged as the most critical intermediate product. Under conditions of low oxygen availability, it was prone to decompose into CO, whereas in the presence of sufficient oxygen, it could undergo further oxidation to form -COOH and subsequently decompose into CO2. Moreover, the reaction chains associated with electrolyte oxidation were found to be highly intricate, characterized by multiple branches and a wide variety of intermediate products. Furthermore, an in-depth analysis was carried out on the generation mechanisms of several typical fire gases. The analysis revealed that CH3OH and C2H5OH could be considered as the characteristic products of the oxidation reactions of DMC and DEC, respectively. It is anticipated that this research will provide a robust theoretical foundation for elucidating the complex reactions involved in LIB fires and offer reaction models for fire simulation purposes, thereby contributing to the enhancement of the safety and reliability of LIBs in various applications.